Analisis Tindak Tutur Ilokusi Dalam Film Pendek “Capciptop! (2020)” Pada Kanal Youtube Ravacana Films - Wina Nurhabibah (Universitas Katolik Widya Karya Malang, 2023)
This study aims to determine (1) the types of illocutionary speech acts in the short film